Perencanaan Produksi Agregat Telur Asin Kelompok Wanita Tani (KWT) Kenanga Kuningan Jawa Barat - Salam, Jaenal Gopur Asmanul; Kartika, Kartika; Nuraeni, Riani (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2024)
The purpose of this study is to forecast demand for salted eggs for the Kenanga Women Farmers Group (KWT) for the next 6 months and a comparison of the level strategy and chase strategy in aggregat planning that can minimize production cost of the Kenanga Women Farmers Group (KWT). The data used in this research is by looking at the historical data of the Kenanga Women Farmer Group (KWT) salted eggs and information related to the research objectives. The data analysis technique is by making a demand forecast using the moving average and exponential smoothing method. Then the forecasting results that have the smallest error rate are used to make aggregate planning using the strategy level method and the chase strategy. The result showed that the production cost of Kenanga Womens Farmers Group (KWT) with the chase strategy method was smaller than the level strategy method, where the production cost with the chase strategy method was Rp. 17.959.950. Weanwhile, the level strategy method is Rp.17.961.817,5. So that the chase strategy method is very suitable to be applied at Kenanga Women Farmer Group (KWT) in minimizing production costs.